CHALLENGES OF PAS THERAPY FOR CORONARY ATHEROSCLEROTIC PLAQUE REVERSAL. (8th October 2012) - Adhikari, Binay Kumar; Meng, Xiaoping
Abstract : Objectives: Coronary artery diseases (CAD) are the major causes of cardiovascular events. Early finding and early treatment of coronary atherosclerotic plaques are critical for preventing cardiovascular events. We used PAS (P: probucol, A: aspirin, S:Statin-atorvastatin) therapy to treat atherosclerotic patients, and obtained significant results regarding plaque reversal. Simultaneously, there is also decreasing potential of ox-LDL and MMP-2 expression. Methods: 150 Patients who visited second Hospital of Jilin University as out-patient or in-patient from February 2008 to February 2011 were selected. They were undergone coronary angiography or coronary CTA examination. Stenosis of at least one branch of coronary artery from 10% to 50% was selected. Before inclusion, they had not used any ipid lowering agents for at least 3 months in a year. Age ranges from 30 to 75 years. All patients were divided into two groups, control (AS) group (100 mg/d aspirin, 20 mg/d atorvastatin), and treatment (PAS) group (0.5 g/d probucol, 100 mg/d aspirin, 20 mg/d atorvastatin). Finally, after follow up for 1 year, stenosis area, plaque length, ox-LDL level and MMP-2 expression of both groups was compared. Results: There is tendency of plaque reversal in both groups. In control group, stenosis area, plaque length, ox-LDL level, MMP-2 level were 0.53+−0.19, 10.62+−3.88, 41.94+−3.8 and 11 114+−10036 respectively, while in treatment (PAS) group, stenosis area, plaque length, ox-LDL level, MMP-2 level were 0.47+−0.41 (p<0.01), 9.36+−3.46 (p<0.01), 26.93+−1.52 (p<0.01) and 7898+−458 (p<0.01) respectively, which means there is significant stastical difference. Conclusions: 1. Both PAS and AS therapy have potential for coronary atherosclerotic plaque reversal along with decreasing tendency for serum ox-LDL, MMP-2 level, but PAS therapy is more potential than AS therapy. 2. PAS (with antioxidant) can be golden combination therapy along with clinically effective and safe drug therapy for plaque reversal.